A chemical closed-loop recycling method of polyester plastic with high efficiency catalysis of white light at room temperature

CN122958262APending Publication Date: 2026-10-23EAST CHINA NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510505628.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-22
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

然而,现有聚酯类塑料回收技术中存在高能耗、反应条件苛刻、产物复杂且分离困难等问题

Benefits of technology

[0022]本发明所记载的技术方案在聚酯材料的化学回收领域具有显著的独特改进性和创新性。传统化学回收方法多依赖高温热解(>150℃)、高压条件或高能耗的紫外/蓝光光源,且通常仅适用于透明或半透明PET材料,对含添加剂、染料或玻璃纤维的复合材料(如包装容器、纺织品)兼容性差。与之相比,本发明的核心创新在于通过白光诱导的钒催化体系,在室温常压下实现了对多种复杂结构PET材料的深度降解。具体而言,钒盐催化剂(如VO(acac)2)在白光激发下通过配体-金属电荷转移(LMCT)机制产生活性氧物种,不仅促进聚酯链的氧化断裂,还能破坏PET的结晶区域,从而克服了传统方法中因材料高结晶度和化学惰性导致的降解效率低、适用范围窄的难题。实验数据表明,该方法对27种真实塑料(包括厚度达3mm的增强容器、含30%-45%玻璃纤维的树脂及黑色PET药品瓶)的降解转化率均超过99%,且产物对苯二甲酸(TPA)的纯度达99%以上(媲美商业级TPA纯度),显著优于现有光催化技术(如蓝光催化体系对黑色PET的降解率仅<50%)。此外,通过溶剂(1,1,2,2-四氯乙烷)的循环回收率>80%,以及百克级放大实验中TPA产率稳定在82%,证明了该技术的工业可行性。本发明采用低成本白光LED(8-200W)和地球丰产的钒盐,能耗降低60%以上,催化剂成本仅为同类金属催化剂的1/10。这些技术突破为PET废塑料的规模化闭环回收提供了高效、经济且环境友好的解决方案。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005369702680000061
    Figure BDA0005369702680000061
  • Figure BDA0005369702680000062
    Figure BDA0005369702680000062
  • Figure BDA0005369702680000071
    Figure BDA0005369702680000071
Patent Text Reader

Abstract

The application discloses a method and system for white-light catalytic polyester plastic at room temperature and normal pressure, wherein a cheap, easily available, low-toxicity, high-yield metal compound is selected as a catalyst, oxygen is used as a green oxidant, and white light is used as a light source, so that waste polyester plastic is efficiently depolymerized into terephthalic acid (TPA) and other monomers, and the method is suitable for green, chemical recycling and resource utilization of waste polyester plastic. The method has the advantages of low energy consumption, low cost, less pollution, good selectivity and the like, and has a wide application prospect in the field of industrialized recycling and treatment of waste polyester plastic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the interdisciplinary field of organic polymer waste resource utilization and advanced photocatalysis technology, and relates to a chemical recycling method for polyester plastics using high-efficiency white light catalysis at room temperature, specifically a green chemical degradation method for polyester plastics based on white light catalysis. Background Technology

[0002] Polyester plastics (especially polyethylene terephthalate (PET)) are among the world's most produced synthetic polymers, widely used in beverage bottles, fiber products, and food packaging due to their excellent mechanical strength, chemical inertness, and processability. However, PET's high stability makes it difficult to degrade in the natural environment. Conventional landfill or incineration can cause environmental problems such as microplastic pollution, water and soil pollution, and emissions of toxic gases like dioxins and greenhouse gases. Existing degradation technologies face significant bottlenecks: traditional pyrolysis requires high temperatures above 300°C to pyrolyze PET, resulting in high energy consumption and poor reaction selectivity; chemical hydrolysis or solvent hydrolysis relies on strong acids, strong alkalis, or high-temperature and high-pressure conditions, easily causing equipment corrosion and secondary pollution; while enzymatic hydrolysis is environmentally friendly, it suffers from low enzyme catalytic efficiency, long reaction cycles (weeks to months), and limited ability to degrade highly crystalline PET. In recent years, photocatalysis technology has become a research hotspot due to its green and low-energy characteristics. However, most systems rely on ultraviolet light excitation (such as TiO2-based catalysts), while ultraviolet light accounts for only a very small proportion (<5%) of the solar spectrum, requiring artificial light sources and resulting in high costs for practical applications. In addition, for hydrophobic and highly crystalline plastics such as polyesters, the active sites on the surface of photocatalysts have difficulty effectively contacting the polymer molecular chains, leading to low interfacial reaction efficiency. Furthermore, the rapid recombination of photogenerated electron-hole pairs further limits the catalytic performance.

[0003] To improve the efficiency of light energy utilization, researchers have developed visible-light-responsive catalysts (such as non-metallic doped materials and heterojunction composites) in an attempt to extend the light absorption range to the main region of the solar spectrum (visible light accounts for about 43%). However, existing polyester plastic recycling technologies suffer from high energy consumption, harsh reaction conditions, complex products, and difficulties in separation. Existing visible-light photocatalytic systems for the degradation of polyester plastics still face multiple challenges: photocatalysts have insufficient ability to capture low-energy photons (such as near-infrared light, which accounts for 52% of the solar spectrum), resulting in low spectral utilization; the lack of specific interactions between the functional groups on the surface of polyester plastics and the catalyst leads to slow mass transfer and adsorption processes; and catalysts are prone to deactivation under complex environmental conditions (such as humidity and temperature fluctuations), restricting their large-scale application. Therefore, developing a white-light or sunlight-driven catalytic system with broad spectral response, high interfacial reactivity, and stability is a key breakthrough for achieving efficient degradation and resource recovery of polyester plastics, and also a pressing technical challenge in the field of environmental catalysis. Summary of the Invention

[0004] To address the shortcomings of existing technologies, this invention provides a method for the degradation and chemical upgrading and recycling of polyester plastics using white light and abundant metal catalysis. This method utilizes visible light to excite a catalyst under mild conditions, activating the alkyl C-H bonds and C-O bonds in polyester plastic molecules, causing them to break and generate oligomers, intermediates, and monomers. Subsequently, under the synergistic effect of catalysts and additives, the degradation intermediates are further converted into high-value-added fine chemicals, such as terephthalic acid (TPA) and its ester derivatives.

[0005] The technical difficulties that needed to be overcome in proposing this invention are as follows: High ester bond stability: PET molecules contain multiple C(O)-O ester bonds with high bond dissociation energies, requiring high temperatures or strong acid / alkali environments for conventional degradation methods; Rigid aromatic skeleton: The aromatic structure of PET leads to strong π-π stacking, hydrogen bonds, and van der Waals forces between and within molecules, resulting in tight molecular arrangement and high crystallinity, further increasing the difficulty of degradation; Diverse raw material sources: Waste polyester plastic products are diverse, including transparent and dark bottles, textiles, composite materials, etc., often containing dyes, auxiliaries, and fillers, leading to complex reaction systems, numerous degradation products, and significant challenges in separation and purification.

[0006] The technical solution described in this invention achieves a breakthrough in efficient capture of a broad spectrum (covering visible light) of 390-780 nm by developing a white light / vanadium catalytic system under room temperature and atmospheric pressure, enabling efficient chemical recycling of polyester plastics at room temperature and atmospheric pressure. This invention addresses the core problems of excessive energy consumption in traditional plastic pyrolysis processes and the narrow spectral response range of conventional photocatalytic systems, providing an innovative solution for the environmentally friendly treatment of waste polyester materials and the recycling of monomer resources.

[0007] This invention provides a method for the chemical closed-loop recycling of polyester plastics using white light catalysis. The method uses abundant metal compounds as catalysts and employs a synergistic catalytic approach of white light and metals in the presence of a solvent to achieve efficient degradation and conversion of polyester plastics.

[0008] The method described in this invention achieves efficient degradation and conversion of waste real polyester plastics, enabling high-value-added degradation and conversion of commercial (waste) PET packaging and textiles, as well as similar structural polyesters (PETG and PBAT).

[0009] In this invention, the method specifically includes the following steps:

[0010] The reaction system of the polyester plastic, abundant metal catalyst and solvent is carried out in an oxygen or air atmosphere with white light simulating sunlight, and high-purity terephthalic acid fine chemical is obtained by alkaline treatment.

[0011] In this invention, the polyester plastics include one or more of polyethylene terephthalate (PET), polybutylene adipate / terephthalate (PBAT), and poly(ethylene terephthalate-1,4-cyclohexadiene dimethyl terephthalate) (PETG).

[0012] The PET can be selected from a single PET material or a mixture of PET and other plastics, and preferably from pure PET or high-purity PET waste.

[0013] In this invention, the abundant metal catalyst includes any one or more of the following: iron-containing catalysts (such as FeCl3), uranium-containing catalysts (such as UO2(NO3)2·6H2O), copper-containing catalysts (such as CuCl2), and vanadium-containing catalysts (such as VO(acac)2, VOSO4, VOC2O4); preferably, it is VO(acac)2.

[0014] In this invention, the solvent includes one or more of hexafluoroisopropanol, dichloromethane, trichloromethane, 1,2-dichloroethane, and 1,1,2,2-tetrachloroethane; preferably, it is 1,1,2,2-tetrachloroethane.

[0015] In this invention, the mass / mass / volume ratio of the polyester plastic, the abundant metal catalyst, and the solvent is 1g:(0.01-0.03)g:(5-20)mL; preferably, it is 1g:0.014g:10mL.

[0016] In this invention, the white light comes from an LED lamp with a wavelength of 390-780nm, a color temperature of 6500K, and a light power of 8W to 200W; preferably, the light power is 50W.

[0017] In this invention, the reaction time is 24-72 hours; preferably, it is 48 hours.

[0018] In this invention, the alkali is a NaOH solution, wherein the concentration of the NaOH solution is 2-3M, preferably 3M.

[0019] In this invention, the alkali treatment time is 1-12 hours; preferably, it is 2 hours.

[0020] In this invention, the reaction can be carried out under oxygen or air conditions, which apply to all steps of the method.

[0021] In specific embodiments of the present invention, Example 1 is a 100-gram-scale reaction, achieving large-scale degradation of waste PET plastic using a photoreactor experimental device; Example 2 is a 10-gram-scale reaction of PET, showing good conversion efficiency and easily recyclable single products for waste PET resins and plastics of different colors, materials, and purities; Example 3 is a condition optimization experiment using PET beverage bottle plastic as a template substrate, comparing the reaction results with different abundant metal catalysts and light wavelengths; Example 4 is the degradation of different PET resins or real plastics, including beverage bottles, detergent bottles, storage boxes, spray bottles, sample bottles, plastic stools, trash cans, medicine bottles, tissue boxes, colored fabrics, and carpets, covering the application range and scenarios of PET plastics (laboratory supplies, medical supplies, and daily necessities (packaging products, textiles)), showing good conversion efficiency and easily recyclable single products for real plastics with different injection molding processes and complex compositions; Example 5 is the degradation of PETG plastic; Example 6 is the degradation of PBAT plastic.

[0022] The technical solution described in this invention has significant unique improvements and innovations in the field of chemical recycling of polyester materials. Traditional chemical recycling methods mostly rely on high-temperature pyrolysis (>150℃), high-pressure conditions, or high-energy-consuming ultraviolet / blue light sources, and are generally only applicable to transparent or semi-transparent PET materials, with poor compatibility with composite materials containing additives, dyes, or glass fibers (such as packaging containers and textiles). In contrast, the core innovation of this invention lies in achieving deep degradation of various complex PET materials at room temperature and atmospheric pressure through a white light-induced vanadium catalytic system. Specifically, vanadium salt catalysts (such as VO(acac)2) generate reactive oxygen species through a ligand-metal charge transfer (LMCT) mechanism under white light excitation, which not only promotes the oxidative breakage of polyester chains but also destroys the crystalline regions of PET, thereby overcoming the problems of low degradation efficiency and narrow applicability caused by the high crystallinity and chemical inertness of materials in traditional methods. Experimental data show that this method achieves a degradation conversion rate exceeding 99% for 27 real plastics (including reinforced containers up to 3mm thick, resins containing 30%-45% glass fiber, and black PET medicine bottles), with the product terephthalic acid (TPA) purity exceeding 99% (comparable to commercial-grade TPA purity), significantly superior to existing photocatalytic technologies (such as blue light catalytic systems with a degradation rate of <50% for black PET). Furthermore, the solvent (1,1,2,2-tetrachloroethane) recycling rate is >80%, and the TPA yield remains stable at 82% in 100g-scale experiments, demonstrating the industrial feasibility of this technology. This invention utilizes low-cost white LEDs (8-200W) and abundant vanadium salts, reducing energy consumption by over 60%, and the catalyst cost is only 1 / 10 of similar metal catalysts. These technological breakthroughs provide an efficient, economical, and environmentally friendly solution for the large-scale closed-loop recycling of waste PET plastics.

[0023] The present invention also provides the application of the above-described method in the separation of plastic degradation and gram-level experiments, the chemical closed-loop recycling of polyester plastics, the pilot-scale 100-gram-level scale-up experiments, and the separation and recycling of mixed plastics.

[0024] The polyester plastics include polyester resins or real polyester plastics, etc.

[0025] The beneficial effects of this invention are: abundant metal catalysis, applicability to PET plastics of various materials, reaction conversion rate >99%, product purity almost identical to commercial purity, recyclable solvent, scale up to hundreds of grams, and use of readily available white light source. Attached Figure Description

[0026] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0027] Figure 1 A schematic diagram illustrating the types of white light / vanadium catalyzed PET plastics described in this invention;

[0028] Figure 2 This is a GPC graph showing the degradation monitoring of PET plastics using the white light / vanadium catalysis method described in this invention.

[0029] Figure 3 The 1H NMR spectrum of TPA, the product of the white light / vanadium catalyzed PET plastic described in this invention;

[0030] Figure 4 This is the carbon NMR spectrum of TPA, the product of the white light / vanadium catalyzed PET plastic described in this invention. Detailed Implementation

[0031] To enable those skilled in the art to better understand the technical solutions of the present invention, the present invention will be further described in detail below with reference to preferred embodiments. It should be noted that the described embodiments are only some embodiments of the present invention, and not all embodiments. The following preferred embodiments should not be considered as limitations on the present invention, and the scope of protection of the present invention should be determined by the scope defined in the claims. For those skilled in the art, several improvements and modifications can be made without departing from the spirit and scope of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

[0032] The following description of at least one exemplary embodiment is merely illustrative and is in no way intended to limit the invention or its application or use. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without inventive effort are within the scope of protection of this invention.

[0033] In all examples shown and discussed herein, any specific values ​​should be interpreted as merely exemplary and not as limitations. Therefore, other examples of exemplary embodiments may have different values.

[0034] This invention proposes a method for photocatalytic degradation of polysulfone plastics. The method uses abundant metals as catalysts and employs photocatalysis to degrade the polysulfone plastics. The method provided by this invention can not only effectively degrade the polysulfone plastics but also convert its degradation products into useful chemicals, achieving resource reuse. Furthermore, the method of this invention has advantages such as being mild, pollution-free, highly efficient, and controllable, and can achieve the degradation of PET plastics without harming the environment, thus having broad application prospects.

[0035] Unless otherwise specified, the experimental materials used in the examples are all conventional biochemical reagents.

[0036] Example 1

[0037] In the white light and vanadium-catalyzed 100g-scale PET degradation and recovery experiment provided by this invention, a PET storage box (100g), VO(acac)2 (1.4wt%, 1.4g), and solvent 1,1,2,2-tetrachloroethane (1.2L) were first added to a 2L batch photoreactor. The reaction system was carried out under white light (6500K, 150W) irradiation, with oxygen continuously introduced at a flow rate of 5mL / min to maintain oxidation conditions, and the reaction was stirred at room temperature for 48 hours. After the reaction, the solvent was recovered by vacuum distillation, and the obtained solid was added to 3.0M NaOH solution (800mL) and stirred for 6 hours. The solution was filtered under vacuum, the organic phase was collected, and 12.0M HCl solution was gradually added to precipitate TPA as a white precipitate. After filtration, the obtained solid was dried in a vacuum oven at 80℃ for 12 hours, finally obtaining high-purity TPA with a yield of 82% (72.8g). Figure 3 The 1H NMR spectrum of the product TPA is shown below. Figure 4 The image shows the carbon NMR spectrum of the product TPA.

[0038] Example 2

[0039] In the 10-gram degradation experiment of PET using white light and vanadium catalysis provided by this invention, a gram-scale reaction was first carried out using 9.6 g of PET as the substrate to verify the degradation performance of PET materials of different colors, materials, and purities. 9.6 g of PET, VO(acac)₂ catalyst (1.4 wt%, 134.4 mg), and 1,1,2,2-tetrachloroethane (100 mL) were added sequentially to a 250 mL three-necked flask. The reaction apparatus was equipped with two 100 W white LED lamps (6500 K) to enhance light intensity and improve the degradation rate, while a glass reflux condenser was used to maintain solvent stability. The experiment was conducted under an oxygen atmosphere with stirring at room temperature for 48 hours. After the reaction, the solid was precipitated by treatment with 3.0 M NaOH for 2 hours, followed by acidification of the filtrate and vacuum drying to obtain high-purity TPA, exhibiting good conversion efficiency and easily recoverable single product.

[0040] PET raw materials Recycled products storage box 7.2g TPA fabric mixture 7.0g TPA gray carpet 8.1g (5.4g TPA + 2.7g fiber)

[0041] Example 3

[0042] This embodiment uses PET beverage bottle plastic (PET 1, purity >99%) as the substrate and systematically optimizes the catalyst type, solvent system, and light conditions to evaluate their effects on PET degradation efficiency and TPA yield. Small 1-5mm plastic particle samples (M...) were selected for the experiment. w =45.9 kg / mol, PDI = 1.93) 192 mg, VO(acac)2 catalyst (1.4 wt%, 3.3 mg) and 1,1,2,2-tetrachloroethane (TeCA, 2.0 mL) solvent were added sequentially to a 25 mL reaction tube or a 4 mL transparent vial, and an oxygen balloon (volume ~2.1 L) was attached. The reaction was stirred for 48 hours under 6500 K white light (18 W). The mixture was treated with 3 M NaOH solution for 2 hours, the filtrate was acidified to precipitate a solid, and vacuum dried to obtain high-purity TPA. Under optimized conditions, PET 1 was efficiently degraded, and the TPA separation yield reached 99%.

[0043] The effects of different catalysts on the degradation of PET 1 were screened, including but not limited to vanadium acetylacetonate (VO(acac)2), vanadium oxalate (VO(C2O4)2), vanadium sulfate (VOSO4), ferric chloride (FeCl3), copper chloride (CuCl2), and uranyl nitrate (UO2(NO3)2·6H2O). VO(acac)2 showed the best catalytic effect, with a TPA yield of 93%, while vanadium oxalate and vanadium sulfate had lower catalytic efficiencies, with TPA yields decreasing to 65-72%. Furthermore, FeCl3 and UO2(NO3)2·6H2O showed good catalytic effects under UV or blue light irradiation, but under white light irradiation, the PET degradation rate decreased significantly, with TPA yields below 50%. The degradation effect of PET was investigated under different light powers (8W, 18W, 30W, 50W). It was found that equivalent degradation could be achieved at powers of 30W and 50W, with TPA yields of 95% and 99%, respectively. When the power was reduced to 8W, the degradation rate decreased, and the TPA yield was 86%. Further screening of different wavelength light sources (blue light 430nm, green light 490nm, red light 650nm) showed that blue light achieved an 81% TPA yield, while green light reduced it to 68%, and red light completely inhibited degradation. The effects of different solvents on the reaction were screened, including but not limited to 1,1,2,2-tetrachloroethane (TeCA), dichloromethane (DCM), and chloroform (CHCl3). The results showed that in TeCA, PET was completely degraded, with the highest TPA yield (93%). DCM could partially dissolve PET, with a TPA yield of 75%, but the degradation rate was slow. CHCl3 yielded a TPA yield of 91%. Furthermore, experiments showed that when using 3.0M NaOH aqueous solution as the reaction medium, PET did not degrade, further verifying that the reaction relies on photocatalytic oxidation rather than alkaline hydrolysis.

[0044]

[0045]

[0046]

[0047] Example 4

[0048] The method for degrading polyester plastics provided by this invention expands the applicable scope of PET degradation, covering PET materials in various application scenarios (laboratory supplies, medical supplies, and daily necessities such as packaging and textiles) including beverage bottles, detergent bottles, storage boxes, spray bottles, sample bottles, plastic stools, trash cans, medicine bottles, tissue boxes, colored fabrics, and carpets. Figure 1The diagram shows the types of PET plastics. PET plastics with different injection molding processes and additives all exhibited high conversion and product recovery rates in this method. First, PET plastics (such as beverage bottles or textile fabrics) were cut into 1-5 mm particles to increase the specific surface area and improve the degradation rate. Then, 192 mg of PET plastic was added to a 25 mL reaction tube, followed by VO(acac)₂ catalyst (1.4 wt%, 3.3 mg) and 1,1,2,2-tetrachloroethane (TeCA, 2.0 mL) solvent, and an oxygen balloon (volume ~2.1 L) was connected. The reaction was irradiated with a white LED lamp (6500 K, 50 W) and stirred at room temperature for 48 hours. After the reaction, the solvent was removed by rotary evaporation, and the resulting solid was added to a 3.0 M NaOH aqueous solution and stirred for 2 hours to promote further dissolution of oligomers and precipitation of the target product. Subsequently, the organic phase was separated by filtration, and 12.0 M HCl solution was added dropwise to precipitate TPA as a white precipitate. The filtered TPA product was dried in a vacuum oven at 80°C for 12 hours to obtain high-purity TPA with a yield of 76-99%.

[0049]

[0050]

[0051]

[0052] Example 5

[0053] This embodiment investigated the degradation behavior of PETG (polyethylene terephthalate copolymer) to evaluate the applicability of the method of the present invention in different polyester systems. PETG powder (233 mg) from an Erlenmeyer flask was used as the substrate. VO(acac)₂ catalyst (1.4 wt%, 3.3 mg) and 1,1,2,2-tetrachloroethane (TeCA, 2.0 mL) solvent were added sequentially to a 25 mL reaction tube, which was then connected to an oxygen balloon (volume ~2.1 L). The reaction was stirred at room temperature and continued for 72 hours under white LED (6500 K, 50 W) irradiation. After the reaction, the solvent was concentrated by rotary evaporation, and 3.0 M NaOH aqueous solution was added. The mixture was stirred at room temperature for 2 hours to further dissolve incompletely degraded oligomers and improve the precipitation efficiency of the target product, terephthalic acid (TPA). The filtrate was acidified to pH 3-5 with 12.0 M HCl, causing TPA to precipitate as a white precipitate. The obtained solid was washed with deionized water, recovered by vacuum filtration, and dried under vacuum at 80°C for 12 hours to finally obtain high-purity TPA (133 mg), with a yield of 80%.

[0054] Example 6

[0055] This embodiment investigated the degradation behavior of PBAT (polybutylene terephthalate-adipate copolymer) to verify the applicability of the method of the present invention in biodegradable polyester materials. PBAT particles (210 mg, approximately 40 mm²) were used in the experiment. 3 Using VO(acac)₂ as the substrate, 1.4 wt%, 3.3 mg of VO₂ catalyst and 2.0 mL of 1,1,2,2-tetrachloroethane (TeCA, 2.0 mL) solvent were added sequentially to a 25 mL reaction tube, which was then connected to an oxygen balloon (volume ~2.1 L). The reaction tube was then stirred at room temperature and reacted continuously for 72 hours under white LED (6500 K, 50 W) irradiation. After the reaction, the solvent was concentrated by rotary evaporation, and 3.0 M NaOH aqueous solution was added. The mixture was stirred at room temperature for 2 hours to further dissolve incompletely degraded oligomers and increase the precipitation rate of the target product, terephthalic acid (TPA). The filtrate was acidified to pH 3-5, causing TPA to precipitate as a white precipitate. The obtained solid was washed with deionized water, recovered by vacuum filtration, and dried under vacuum at 80 °C for 12 hours to finally obtain high-purity TPA (54 mg), with a yield of 65%.

[0056] Compare with Example 1

[0057] This comparative example investigated the oxidative degradation behavior of PET to verify the efficient degradation capability of the iron-catalyzed system in complex polyester materials. Transparent PET powder (384.4 mg, 2.0 mmol, Mw = 25 kDa, 200 mesh) was selected as the substrate. FeCl3 catalyst (0.5 mol%, 1.7 mg) and 1,2-dichloroethane (DCE, 10.0 mL) solvent were added sequentially to a 50 mL sealed tube, and concentrated hydrochloric acid (85 μL, 1.0 mmol) was injected under an oxygen balloon (1 atm). The reaction mixture was continuously stirred in an oil bath at 85 °C for 24 hours under 390 nm blue LED light (100 W) irradiation, promoting the cleavage of PET chains through the oxidative activity of the iron catalyst. After the reaction, 3 M NaOH solution was added to adjust the pH to 10-11, fully dissolving the undegraded oligomers and generating terephthalic acid (TPA). The filtrate was then acidified with concentrated hydrochloric acid to pH 3-4, precipitating a white solid. After vacuum filtration, washing with deionized water and vacuum drying at 40°C, high-purity TPA was finally obtained with a yield of 97%.

[0058] Comparative Example 1 primarily targets transparent PET powder. For colored or composite PET materials, the catalyst loading needs to be increased (5 mol% FeCl3), and the yield decreases significantly (e.g., only 37% for blue detergent bottles). This invention can efficiently degrade 27 complex PET materials, including colored textiles, colored PET packaging, and glass fiber reinforced resin, demonstrating broader industrial applicability. Comparative Example 1 requires a high temperature of 85°C (oil bath heating), while this invention only requires room temperature, significantly reducing energy consumption and simplifying the operation process. The comparative example relies on a specific wavelength of blue light (390nm), requiring dedicated LED equipment; this invention uses ordinary white LEDs (6500K), with lower light source costs and easier availability. Comparative Example 1 requires concentrated hydrochloric acid (50 mol%) as a co-catalyst, increasing the burden of waste acid treatment; this invention only requires oxygen as a green oxidant, making it more environmentally friendly. This invention, with its core advantages of mild conditions, broad spectrum compatibility, efficient decomposition, and scalability potential, provides a more economical, universal, and sustainable solution for the resource recovery of complex PET waste, fully demonstrating the innovation and practicality of the technical solution.

[0059] Unless otherwise defined, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used in this specification is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.

[0060] As used in this invention, the term "comprising" is an open-ended expression, meaning it includes the contents specified in this invention but does not exclude other aspects.

[0061] As used in this invention, the term "and / or" includes any one or more of the related listed items and all combinations thereof.

[0062] The scope of protection of this invention is not limited to the above embodiments. Any variations and advantages that can be conceived by those skilled in the art without departing from the spirit and scope of this invention are included in this invention and are protected by the appended claims.

Claims

1. A method for the chemical closed-loop recycling of polyester plastics using white light catalysis, characterized in that, The method uses abundant metal compounds as catalysts and employs a white light and metal synergistic catalysis method in the presence of a solvent to achieve efficient degradation and conversion of polyester plastics.

2. The method as described in claim 1, characterized in that, The method specifically includes the following steps: The reaction system of the polyester plastic, abundant metal catalyst and solvent is carried out in an oxygen or air atmosphere with white light simulating sunlight. After the reaction is completed, it is treated with alkali to obtain high-purity terephthalic acid fine chemicals.

3. The method as described in claim 1 or 2, characterized in that, The polyester plastics include any one or more of polyethylene terephthalate (PET), polybutylene adipate / terephthalate (PBAT), and poly(ethylene terephthalate-1,4-cyclohexadiene dimethyl terephthalate) PETG; and / or The solvent includes one or more of hexafluoroisopropanol, dichloromethane, trichloromethane, 1,2-dichloroethane, and 1,1,2,2-tetrachloroethane.

4. The method as described in claim 1 or 2, characterized in that, The high-yield metal catalyst includes any one or more of the following: iron-containing catalysts, uranium-containing catalysts, copper-containing catalysts, and vanadium-containing catalysts.

5. The method as described in claim 4, characterized in that, The high-yield metal catalyst includes any one or more of FeCl3, UO2(NO3)2·6H2O, CuCl2, VO(acac)2, VOC2O4, and VOSO4.

6. The method as described in claim 1 or 2, characterized in that, The mass / mass / volume ratio of the polyester plastic, the high-yield metal catalyst, and the solvent is 1g:(0.01-0.03)g:(5-20)mL.

7. The method as described in claim 1 or 2, characterized in that, The white light comes from LED lights, with a wavelength of 390-780nm and a light power of 8-200W.

8. The method as described in claim 2, characterized in that, The reaction time is 24-72 hours.

9. The method as described in claim 2, characterized in that, The alkali is a NaOH solution, wherein the concentration of the NaOH solution is 2-3M; and / or, the alkali treatment time is 1-12 hours.

10. The application of the method according to any one of claims 1-9 in the separation of plastic degradation and gram-level experiments, the chemical closed-loop recycling of polyester plastics, the pilot-scale gram-level amplification experiments, and the separation and recycling of mixed plastics.